1990
DOI: 10.1007/bf00572184
|View full text |Cite
|
Sign up to set email alerts
|

The influence of motor unit composition and stature on fractionated patellar reflex times in untrained men

Abstract: The purpose of the present study was to investigate the influence of muscle fibre composition and stature on fractionated patellar reflex times in ten healthy untrained men (mean age: 23.3 years, SD 3.1; mass: 65.9 kg, SD 8.5; height: 172.3 cm, SD 5.3). Biopsies were taken from the right vastus lateralis muscle. Using staining for myofibrillar adenosine triphosphatase after pre-incubation at pH 4.3 and 4.6, muscle fibres were classified into slow twitch (ST), fast twitch, oxidative-glycolytic (FTa) and fast tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…are within a similar range to those reported previously (Ryushi, Fukunaga, Yuasa, & Nakajima, 1990). In comparison with the mean total reflex time of 89.9 ms, the mean conscious response time of 175.1 ms was significantly slower (t = 18.430, df = 68, P < .001) with no overlap between distributions.…”
Section: Resultssupporting
confidence: 88%
“…are within a similar range to those reported previously (Ryushi, Fukunaga, Yuasa, & Nakajima, 1990). In comparison with the mean total reflex time of 89.9 ms, the mean conscious response time of 175.1 ms was significantly slower (t = 18.430, df = 68, P < .001) with no overlap between distributions.…”
Section: Resultssupporting
confidence: 88%
“…Whereas in the other study (Ryushi et al, 1990) given that they used a more limited height range (16 cm) of subjects than we employed: 24 cm, where our more expansive height range would be expected to increase the likelihood for detection of stature-dependent effects. One possible reason for both the larger and stature dependent latency reported by Ryushi et al (1990) is that their sample population was (presumably) exclusively Japanese in origin, whereas ours was entirely Caucasian. This effect of ethnicity is supported by the similarity of our male latency to that of Viitasalo and Komi (1981) who, like us, also sampled from a predominantly Caucasian (in their case Finnish) population.…”
Section: Sexual Dimorphism Of Latencymentioning
confidence: 94%
“…It has been shown that slow motor units are stier than fast motor units, in rats (Goubel and Marini 1987) and in humans (Ryushi et al 1990). It is likely that the recruitment of weaker slow motor units, probably emitting lower amplitude elementary PMG, for the highest stimulation intensities is compensated for by a greater rate of increase of stiness.…”
Section: Evoked Pmg and Forcementioning
confidence: 98%
“…That would largely explain the latency decrease with recruitment documented here. Because the slowest motor units have been suggested to have a higher passive stiness (Ryushi et al 1990), muscle tension generated by an increasing number of recruited slow units would be better transmitted through a stier muscle medium and tendon. The decrease of PMG and force delays accompanying recruitment would suggest that they have a common origin, the stretching of the series elastic element (from sarcomere to ®nger) adding a constant delay.…”
Section: Latenciesmentioning
confidence: 98%